**Given:**

The sequence is
an+1=an−an−1
. (1)

The first term of the sequence is
a1=2
.

The second term of the sequence is
a2=1
.

**Calculation:**

Obtain the third term of the sequence.

Substitute 2 for *n* in equation (1).

a2+1=a2−a2−1

a3=a2−a1
(2)

Substitute 1 for
a2
and 2 for
a1
in equation (2).

a3=1−2=−1

Thus, the fourth term of the sequence is
a3=−1_
.

Obtain the second term of the sequence.

Substitute 3 for *n* in equation (1).

a3+1=a3−a3−1

a4=a3−a2
(3)

Substitute −1 for
a3
and 1 for
a2
in equation (3).

a4=−1−1=−2

Thus, the fourth term of the sequence is
a4=−2_
.

Obtain the fifth term of the sequence.

Substitute 4 for *n* in equation (1).

a4+1=a4−a4−1

a5=a4−a3
(4)

Substitute −2 for
a4
and −1 for
a3
in equation (4).

a4=−2−(−1)=−2+1=−1

Thus, the fifth term of the sequence is
a5=−1_
.

Therefore, the first five terms of the sequence are
2,1,−1,−2,−1
.